1990
DOI: 10.1016/0163-6383(90)90016-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in neonatal state and lateralized head orientation

Abstract: Abstract:Sex differences in state and head orientation were examined 10 to 22 hours after birth for 50 healthy, full-term, normal, vaginally delivered neonates. None of the males had been circumcised at the time of testing. The procedure required videotaping for 30 min in three different conditions: supine, seated in an infant seat (inclined 35°), and seated in an assistant,s lap after having arms or legs manipulated for 10 s. Videotapes were analyzed for direction of infant,s head orientation and state. Males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The organization of state behavior has often been used as an index of the integrity of the central nervous system [8,23]. The sex differences in waking behavior reported here and in previous studies [8,9] suggest sex differences in the maturation of the central nervous system.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The organization of state behavior has often been used as an index of the integrity of the central nervous system [8,23]. The sex differences in waking behavior reported here and in previous studies [8,9] suggest sex differences in the maturation of the central nervous system.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, Harkins, et. al [9] found that female infants remain in "quiet alert" states longer than male infants who exhibit more crying and sleeping as well as more frequent state transitions. Taken together, these studies suggest that the integrity of the female nervous system provides briefer and calmer transitions into wakefulness thereby providing longer periods of quiet alertness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female infants continue to show increased attention, focusing, and perceptual sensitivity when compared to males (Else-Quest, Shibley Hyde, Hill Goldsmith, & Van Hulle, 2006). With the male infants' more irritable, fussy state, they show an increased tendency to sleep less, cry more, grimace, show anger, fuss, want to be picked up, kick, and use more motor movements (Michel, Harkins, & Meserve, 1990;Silverman, 1987;Weinberg et al, 1999, p. 16). Male infants appear to have more difficulty selfcomforting, and more trouble with states of overarousal and excitement, and, in general, demonstrate greater lability in their emotions and problems regulating their affectivity when com-pared to females (Weinberg et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/termsand-conditions Michel, Harkins, & Meserve, 1990;Ronnquist & Hopkins, 1998), demonstrate greater grasping strength in their right hand (Petrie & Peters, 1980;Tan, Ors, Kurkcuoglu, & Kutlu, 1992), and will grasp an object for significantly longer in their right hand than in their left hand (Caplan & Kinsbourne, 1976;Petrie & Peters, 1980). In addition, some research shows that young infants are more likely to step with their right foot first during elicitation of a stepping reflex (Melekian, 1981;Peters & Petrie, 1979).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%